The development of Anglo - Japanese trade (Japan, 1990)
Thisbrief record will try to link together some of the outstanding events in Japan's economic and social growth, to trace a little of the hostory of the great and world-famous house of Mitsui, symbolising all that is best in the industrial and commercial prosperity of the nation, and to consider the commercial relationships between Japan and Great Britain.
Keywords: Great Britain,Japan,Anh,Nhật Bản; International economic relationship,International economic relationship,Quan hệ kinh tế quốc tế,Quan hệ kinh tế quốc tế; Japan,Great Britain,Nhật Bản,Anh